2020
DOI: 10.1371/journal.pone.0229587
|View full text |Cite
|
Sign up to set email alerts
|

Movement behavior remains stable in stroke survivors within the first two months after returning home

Abstract: Background and purpose The aim of this study is to investigate changes in movement behaviors, sedentary behavior and physical activity, and to identify potential movement behavior trajectory subgroups within the first two months after discharge from the hospital to the home setting in first-time stroke patients. Methods A total of 140 participants were included. Within three weeks after discharge, participants received an accelerometer, which they wore continuously for five weeks to objectively measure movemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 65 publications
(82 reference statements)
0
2
0
Order By: Relevance
“…In line with prior studies, the current data show that stroke survivors are predominantly sedentary and engage in little moderate to vigorous PA (34,35). The current findings are similar to those of the study of Wondergem et al (36), who reported SB and PA levels from free-living stroke survivors in the first 2 months post-stroke. Compared with the few other studies that have objectively assessed levels of SB and PA (35,37) among stroke survivors, the current study population appears to be more physically active, on average, in terms of less time spent sedentary and more time spent in moderate PA. After adjustments for probable factors affecting PA post-stroke, this study found no significant relationship between SB, PA, and mood.…”
Section: Discussionsupporting
confidence: 92%
“…In line with prior studies, the current data show that stroke survivors are predominantly sedentary and engage in little moderate to vigorous PA (34,35). The current findings are similar to those of the study of Wondergem et al (36), who reported SB and PA levels from free-living stroke survivors in the first 2 months post-stroke. Compared with the few other studies that have objectively assessed levels of SB and PA (35,37) among stroke survivors, the current study population appears to be more physically active, on average, in terms of less time spent sedentary and more time spent in moderate PA. After adjustments for probable factors affecting PA post-stroke, this study found no significant relationship between SB, PA, and mood.…”
Section: Discussionsupporting
confidence: 92%
“…40 In this study movement behavior patterns were objectified in the first three weeks after returning home. Although movement behavior outcomes remain stable within the first two months after returning home in people with a first ever-stroke, 41 individuals change movement behavior patterns. Therefore, future research should determine if individuals' membership changes in movement behavior patterns within the first year after discharge to home.…”
Section: Discussionmentioning
confidence: 98%
“…3 Behavioural change and environmental approaches are effective in reducing sedentary behaviour, 4,5 but published studies on the effectiveness from discharge until follow-up are few, and evidence is sparse. 6 Since sedentary behaviour is more common in patients with minor ischeamic stroke than in healthy individuals, 7 it is necessary to clarify the effectiveness of approaches to reduce sedentary behaviour in this cohort. Although we previously established the effectiveness of an approach to promote the reduction of sedentary behaviour in patients with minor ischaemic stroke, 8 the sample size was small, suggesting the need for further study.…”
Section: Introductionmentioning
confidence: 99%